Positionality, Epstemology, and Social Justice in the Classroom - Takacs, David (Social justice, 2002)
Part of a special section on new pedagogies for social change. By asking the question, “How does who you are and where you stand in relation to others shape what you know about the world?” in his courses at California State University, Monterey Bay, the writer aims to open up new possibilities for students to understand their connection with the world. By examining the dialogues on whether an individual's positionality can bias his/her epistemology, he demonstrates that people come to learn that their views may be constrained by the narrow range of experiences they have had. He contends that people become more willing to talk with others once they realize that their own positionality is biased by individual experiences, and that this must also influence their perception; and that people come to know the world more fully by knowing how they know the world.